Strategi Internalisasi Nilai Islam Melalui Bermain Edukatif di TK Babussalam Kisaran - Rahmi, Maulida; Rahman, Mhd. Habibu (Medan Resource Center, 2025)
This study aims to explore the internalization of Islamic values through educational play activities at Babussalam Kisaran Private Kindergarten. Employing a descriptive qualitative method, the research involved 10 early childhood education teachers and was conducted over a three-month period. Data were collected through observation, interviews, and documentation. The findings reveal that educational play activities—such as Islamic role-play, Islamic-themed educational games, and singing Islamic songs—serve as effective mediums for value transmission. The core Islamic values internalized include faith (iman), worship (ibadah), moral conduct (akhlak), and social interaction. Teachers utilized various strategies including role modeling, Islamic storytelling, positive reinforcement, and interactive play-based approaches tailored to the developmental stages of early childhood learners. A key contribution of this study lies in its practical demonstration of how Islamic character education can be innovatively embedded into daily play activities in PAUD (Early Childhood Education), offering a culturally relevant and pedagogically sound model. Despite its promising findings, the study is limited to a single institution and a relatively short observation period, suggesting the need for broader and longitudinal research in future studies.